Working the Angels The Shape of Pastoral Integrity - Peterson, Eugene H. (Grand Rapids, Mich. William B . Eerdmans Publishing Company, 1987)
"In Working the Angles, Peterson calls the attention of his fellow pastors to three basic acts--which he sees as the three angles of a triangle--that are so critical to the pastoral ministry that they determine the shape of everything else. The acts--pr
Keywords: Pastoral theology. Theology. Ministry -- Ethical aspects